The Evolution of Digital Arrest Scams and Their Impact on Privacy Rights Guaranteed Under Constitution of India - Upendra Grewal, Anuprash Rajat (Journal of Neonatal Surgery, 2025)
In recent years, the emergence of “digital intrusion games” has put personal security and privacy at serious risk. What began as simple phishing emails has evolved into more sophisticated techniques, with scammers now using new technologies to circumvent the law and trick victims into giving up money or confidential information. This study looks at how these scams have evolved – from basic email scams to complex operations that involve data mining, social engineering and even artificial intelligence. The damage goes far beyond economic loss. These fraudulent practices violate privacy on a massive scale, leaving victims vulnerable and confused. Using social media and print media, criminals make claims that blur the line between law enforcement and freedom. The result? Growing distrust of law enforcement agencies and increasing concerns about privacy in the digital age. Through case studies and current trends, the study also examines the psychology behind victimisation and the wider societal impact of these scams. It examines existing privacy laws and asks whether they are strong enough to deal with these constantly changing threats. Ultimately, the article calls for urgent action – better digitisation and stronger legal protections – to protect privacy in an age where technology is as easy to use as it is to obtain. By empowering citizens and building resilience, we can combat digital exploitation and protect the fundamental right to privacy. In recent years, the emergence of “digital intrusion games” has put personal security and privacy at serious risk. What began as simple phishing emails has evolved into more sophisticated techniques, with scammers now using new technologies to circumvent the law and trick victims into giving up money or confidential information. This study looks at how these scams have evolved – from basic email scams to complex operations that involve data mining, social engineering and even artificial intelligence. The damage goes far beyond economic loss. These fraudulent practices violate privacy on a massive scale, leaving victims vulnerable and confused. Using social media and print media, criminals make claims that blur the line between law enforcement and freedom. The result? Growing distrust of law enforcement agencies and increasing concerns about privacy in the digital age. Through case studies and current trends, the study also examines the psychology behind victimisation and the wider societal impact of these scams. It examines existing privacy laws and asks whether they are strong enough to deal with these constantly changing threats. Ultimately, the article calls for urgent action – better digitisation and stronger legal protections – to protect privacy in an age where technology is as easy to use as it is to obtain. By empowering citizens and building resilience, we can combat digital exploitation and protect the fundamental right to privacy.